Cost-benefit analysis of investment projects - Flynn, Theresa (Archives of Business Research, 2020)
The paper contents included considerations of the relationships existing between business units of Multinational Organizations (MNOs). Relevant economic theory provided a framework for the review of accounting practices. An example of consequences derived as the result of transfer pricing strategies compared with the transaction costs of pharmaceutical MNO GlaxoSmithKline (GSK) was provided.